Phytochemistry and Pharmacology of Calotropis gigantea — An update (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Calotropis gigantea is a perennial herb known for its applications in traditional medicine. It has been efficiently used in Ayurveda, Unani, and Siddha medicinal systems for years. All the plant parts have been used as medicine owing to its analgesic, anthelmintic, astringent, anti-inflammatory, wound healing, sedative, anti-asthmatic, antimicrobial, antioxidant, procoagulant, hepatoprotective, hypoglycemic, and pregnancy interceptive properties. For instance, the leaves, latex, flowers, stem bark, root of the plant are used as expectorant, depilatory, in leprosy scabies of the scalp, eruptions on the body, piles, asthma, liver and spleen enlargement, and painful joint swellings. Moreover, the plant is beneficial for the treatment of various diseases including tumors, ulcers, and piles thereby providing great opportunity to be used in pharmaceutical industry for modern drug synthesis. Phytochemical constituents of the plant responsible for its pharmacological activities include alkaloids, triterpenoids, flavonoids, saponins, steroids, alcohol, fatty acids, esters of calotropeols, glycosides and proteases. Besides, there is a strong correlation between the chemical structures and therapeutic activity of C. gigantea. Therefore, present review tries to give a brief description of its phytochemical composition, ethnobotanical characteristics, and pharmacological activity.